More than teacher directed or child initiated: Preschool curriculum type, parent involvement, and children’s outcomes in the child-parent centers. - Graue, Elizabeth; Clements, Melissa A.; Reynolds, Arthur J.; Niles, Michael D. (Education Policy Analysis Archives, 2004)
This study investigated the contributions of curriculum approach and parent involvement to the short- and long-term effects of preschool participation in the Title I Chicago Child-Parent Centers. Data came from the complete cohort of 989 low-income children (93% African American) in the Chicago Longitudinal Study, who attended preschool in the 20 Child-Parent Centers in 1983-1985 and kindergarten in 1985-1986. We found that implementation of an instructional approach rated high by Head Teachers in teacher-directed and child-initiated activities was most consistently associated with children’s outcomes, including school readiness at kindergarten entry, reading achievement in third and eighth grades, and avoidance of grade retention. Parent involvement in school activities, as rated by teachers and by parents, was independently associated with child outcomes from school readiness at kindergarten entry to eighth grade reading achievement and grade retention above and beyond the influence of curriculum approach. Findings indicate that instructional approaches that blend a teacher-directed focus with child-initiated activities and parental school involvement are origins of the long-term effects of participation in the Child-Parent Centers.